PERANCANGAN MOBILE AR DAN 3D VR WALKTHROUGH SEBAGAI MEDIA INFORMASI KAMPUS STEKOM SEMARANG BERBASIS ANDROID - Yuli Fitrianto (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Abstract The development of technology has entered the digital era of mobile, which required information media is more than just print brochures and official website, because it offered a solution for the design of a medium that can be run through mobile devices based on Android that are engaging, interactive, and follow the latest technology that augmented reality and virtual reality. The method used in this design is the System Development Life Cycle or SDLC, while supporting software used is Unity3D and Vuforia. Results from this study is the successful mobile AR and 3D-VR Walkthrough to implement and complete the on-campus media STEKOM information which has been used.